Studi Intensitas Pencahayaan Terhadap Puncak Produksi Ayam Petelur Fase Layer di UD. Mahakarya Farm Banyuwangi - Erfan Kustiawan; Dyah Laksito Rukmi; Shokhirul Imam; Sandi Owen Permadi (Politeknik Negeri Jember, 2019)
The objective of this case study was to evaluate good lighting levels in laying hens. The data were collected for three months at UD. Mahakarya Farm Banyuwangi. A total of 4.400 heads of layer chicken were used in this study. The lighting intensityused were 15 lux in cage A and 10 lux in cage B. The average of egg production were75.91% and 73.57% for cage A (15 lux) and cage B (10 lux), respectively. The average of egg weight were 59.37 g and 59.23 gfor cage A (15 lux) and cage B (10 lux), respectively. The results of this study presented that layer chicken aged 25 weeks produced better production efficiency values by 10 lux. At the end of production period(38 weeks) increased production efficiency by 15 lux.